Imaging chronic traumatic brain injury as a risk factor for neurodegeneration. (1st June 2014) - Little, Deborah M.; Geary, Elizabeth K.; Moynihan, Michael; Alexander, Aristides; Pennington, Michelle; Glang, Patrick; Schulze, Evan T.; Dretsch, Michael; Pacifico, Anthony; Davis, Matthew L.; Stevens, Alan B.; Huang, Jason H.
Abstract: Population‐based studies have supported the hypothesis that a positive history of traumatic brain injury (TBI) is associated with an increased incidence of neurological disease and psychiatric comorbidities, including chronic traumatic encephalopathy, Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis. These epidemiologic studies, however, do not offer a clear definition of that risk, and leave unanswered the bounding criteria for greater lifetime risk of neurodegeneration. Key factors that likely mediate the degree of risk of neurodegeneration include genetic factors, significant premorbid and comorbid medical history (e.g. depression, multiple head injuries and repetitive subconcussive impact to the brain, occupational risk, age at injury, and severity of brain injury). However, given the often‐described concerns in self‐report accuracy as it relates to history of multiple TBIs, low frequency of patient presentation to a physician in the case of mild brain injuries, and challenges with creating clear distinctions between injury severities, disentangling the true risk for neurodegeneration based solely on population‐based studies will likely remain elusive. Given this reality, multiple modalities and approaches must be combined to characterize who are at risk so that appropriate interventions to alter progression of neurodegeneration can be evaluated. This article presents data from a study that highlights uses of neuroimaging and areas of needed research in the link between TBI and neurodegenerative disease.